Neurohumoral Biomarker Profile Associated With Blood Pressure Response After Renal Denervation - Wei Liang; Yingdong Wang; Long Ai; Runmin Sun; Xu Zhao; Heng Yu; Xiaofang Zhang; Caie Li; Jianshu Chen; Ruixin Ma; Qiongying Wang; Xiaowei Zhang; et al. (The Journal of Clinical Hypertension, 2026)
ABSTRACT Blood pressure (BP) response after renal denervation (RDN) remains heterogeneous. This study explored whether baseline neurohumoral and inflammation‐related biomarkers were associated with a pronounced ambulatory BP response after RDN. This single‐center post hoc analysis included 40 patients with uncontrolled essential hypertension who underwent RDN in four clinical trial programs. High response was defined as a reduction of ≥10 mmHg in 24‐h ambulatory systolic blood pressure (24‐h SBP) at 6 months. Baseline clinical, anatomical, procedural, and biomarker variables were compared between high‐ and low‐response groups. Logistic regression and receiver operating characteristic analyses were performed to evaluate candidate biomarkers. RDN was associated with reductions in ambulatory BP at 24 h and 6 months. At 6 months, office SBP and diastolic blood pressure (DBP) decreased by 21.57 ± 9.90, 9.70 ± 9.94 mmHg, and 24‐h ambulatory SBP and DBP decreased by 14.38 ± 13.55/9.25 ± 8.57 mmHg. BP reductions were broadly comparable across the four catheter subgroups. Baseline sex, age, ablation number, renal artery diameter and length, aldosterone did not differ between response groups. High responders had higher baseline upright plasma renin activity, 24‐h urinary norepinephrine, serum neuropeptide Y, and plasma adenosine triphosphate levels. These four biomarkers were associated with high response in logistic regression, and their combined model showed high apparent discrimination. Patients with a pronounced ambulatory BP response after RDN showed a biomarker profile consistent with higher neurohumoral activation. This profile may help characterize RDN responsiveness, but validation in larger prospective cohorts is required.